The RecF pathway of homologous recombination can mediate the initiation of DNA damage-inducible replication of the Escherichia coli chromosome. - Asai, T (1994)
DNA damage-inducible DNA replication in SOS-induced Escherichia coli cells, termed inducible stable DNA replication (iSDR), has previously been shown to require either the RecBCD or the RecE pathway of homologous recombination for initiation. Here, we demonstrate that recB recC sbcC quadruple mutant cells are capable of iSDR induction and that a mutation in the recJ gene abolishes the inducibility. These results indicate that the RecF pathway of homologous recombination can also catalyze iSDR initiation.